Understanding the Sexual and Reproductive Health Experiences of Refugee and Host Community Adolescents and Youth in Rwanda During COVID-19: Needs, Barriers, and Opportunities - Meyer, Katherine; Abimpaye, Monique; Harerimana, Jean de Dieu; Williams, Christina; Gallagher, Meghan C. (Frontiers in Reproductive Health, 2022)
Background COVID-19 has exacerbated the sexual and reproductive health (SRH) needs of those affected by humanitarian emergencies, particularly affecting adolescents and youth, whose needs are often neglected during crises. In Rwanda, the situation for refugees in Mahama Refugee Camp has worsened, as COVID-19 lockdown measures have increased needs while restricting access to basic services. Few assessments have been conducted on the SRH needs of refugees in Mahama camp, including adolescents and youth, since COVID-19. To address this gap, Save the Children (SC) undertook research utilizing SenseMaker to collect data on the SRH needs of adolescents and youth in Mahama camp, as well as in the surrounding host community. Methodology SC used SenseMaker to collect 745 data entries from adolescents and youth in Mahama camp and the surrounding host community. The application was pretested with adolescents and youth in Mahama camp, before initiating the research. SenseMaker asks participants to share their stories in response to a prompt; our prompt asked participants to describe their experience seeking help with their health during COVID-19. The research team analyzed the data using simultaneous coding to examine key themes. The results were discussed with SC staff to validate the coding analysis results before conducting four focus group discussions to further clarify results and propose action steps in response to the findings. Results Many adolescents and youth reported significant difficulties accessing SRH information and services, including stigmatization among service providers. Provider biases and negative attitudes were repeatedly cited as barriers. Stories collected during COVID-19 show how these biases and judgmental attitudes continue to adversely affect access and use of SRH services for young people. Coercive, non-consensual, and transactional sexual incidents were widely reported from adolescents and youth. They cited reduced time in education spaces as a source of distress as well as increasing their level of sexual activity and associated risks. Limited data exists for SRH needs among adolescents and youth during COVID-19 in humanitarian settings. This study adds to the evidence, making the case for increased SRH prioritization for adolescents and youth in humanitarian settings, particularly when facing overlapping crises like during the COVID-19 pandemic.